Kepercayaan Pantangan Makanan dan Keragaman Pangan dengan Kejadian KEK pada Ibu Hamil di Wilayah Kerja Puskesmas Talise - Nur Wahyu Qamariyah; Ni Ketut Kariani; Nurdiana Nurdiana (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The World Health Organization (WHO) says that the incidence of Chronic Energy Deficiency (CED) in pregnant women globally ranges from 35-75%. In Indonesia, the prevalence of CED in 2023 was 16.9% and in Central Sulawesi it was 21.3%. In 2022, Talise Public Health Center was in the highest ranks regarding prevalence of CED, it was 25.99%. This study aims to analyze the correlation between food taboo beliefs and food diversity toward the incidence of CED in pregnant women in the Talise Public Health Center working area.This type of research is quantitative using a case control design with a population of all pregnant women with CED. This research was conducted in November 2024. The total of sample was 32 respondents that taken by using total sampling technique. Based on the results of the chi square test on food taboo beliefs that p-value = 0.210> ∝ 0.05, then on food diversity had p-value = 0.022 < ∝ 0.05 value. There is a correlation between food diversity and the incidence of CED among pregnant women in the Talise Public Health Center working area.